Evaluation of effect of low level laser therapy with intracanal medicament on periapical healing: A randomised control trial - Deep Shah; Muckatira Cariappa Ponappa; Kongettira Chittiappa Ponnappa (Wolters Kluwer Medknow Publications, 2021)
Objective(s): Photobiomodulation, also commonly referred to as low level laser therapy (LLLT), uses light energy to elicit biological responses from the cell and normalise cell function. Using LLLT on bone has been demonstrated to be effective in modulating inflammation, accelerating bone cell proliferation and enhancing the healing process. The objectives of this study were to evaluate postoperative pain and periapical healing in two different groups. Materials and Methods: 40 subjects with periapical lesion were selected and were assigned randomly into two groups. Group I: Conventional root canal therapy along with LLLT. Group II: Conventional root canal therapy only. Radiographs were obtained and assessed at baseline, 3, 6 and 9 months postoperatively. The VAS pain scale was assessed post operatively at 0, 7th and 14th day respectively. The Independent t-test was used for evaluation of the data. Results: Significant differences were noted in reduction of periapicallesion at 3 and 9 months follow-up. The healing was better in Group I that received LLLT with the conventional Root Canal Treatment (RCT). Values for postoperative pain was lower in Group I than Group II, but were statistically non-significant. Conclusion(s): LLLT when used as an adjunct with conventional root canal treatment showed acceleration of the healing process of periapical lesions. LLLT has a positive effect on modulating the immune response for favourable healing.